Study of the outcome of suicide attempts: characteristics of hospitalization in a psychiatric ward group, critical care center group, and non-hospitalized group - Kemuyama Nobuo; Yagi Junko; Koeda Atsuhiko; Kawamura Sachiyo; Nakamura Hikaru; Yambe Takehito; Isono Hisayasu; Yoshida Tomoyuki; Endo Jin; Otsuka Kotaro; Kudo Kaoru; Harada Hisako; et al. (BMC Psychiatry, 2010)
Abstract Background The allocation of outcome of suicide attempters is extremely important in emergency situations. Following categorization of suicidal attempters who visited the emergency room by outcome, we aimed to identify the characteristics and potential needs of each group. Methods The outcomes of 1348 individuals who attempted suicide and visited the critical care center or the psychiatry emergency department of the hospital were categorized into 3 groups, "hospitalization in the critical care center (HICCC)", "hospitalization in the psychiatry ward (HIPW)", or "non-hospitalization (NH)", and the physical, mental, and social characteristics of these groups were compared. In addition, multiple logistic analysis was used to extract factors related to outcome. Results The male-to-female ratio was 1:2. The hospitalized groups, particularly the HICCC group, were found to have biopsychosocially serious findings with regard to disturbance of consciousness (JCS), general health performance (GAS), psychiatric symptoms (BPRS), and life events (LCU), while most subjects in the NH group were women who tended to repeat suicide-related behaviors induced by relatively light stress. The HIPW group had the highest number of cases, and their symptoms were psychologically serious but physically mild. On multiple logistic analysis, outcome was found to be closely correlated with physical severity, risk factor of suicide, assessment of emergent medical intervention, and overall care. Conclusion There are different potential needs for each group. The HICCC group needs psychiatrists on a full-time basis and also social workers and clinical psychotherapists to immediately initiate comprehensive care by a medical team composed of multiple professionals. The HIPW group needs psychological education to prevent repetition of suicide attempts, and high-quality physical treatment and management skill of the staff in the psychiatric ward. The NH group subjects need a support system to convince them of the risks of attempting suicide and to take a problem-solving approach to specific issues.